Bilirubin Induces Pain Desensitization in Cholestasis by Activating 5-Hydroxytryptamine 3A Receptor in Spinal Cord - Kong, Erliang; Wang, Hongqian; Wang, Xiaoqiang; Zhang, Yan; Zhang, Jinmin; Yu, Weifeng; Feng, Xudong; Sun, Yuming; Wu, Feixiang (Frontiers in Cell and Developmental Biology, 2021)
Background Cholestasis patients often suffer from pain desensitization, resulting in serious complications in perioperative period. This study was aim to investigate the mechanism of bilirubin in cholestasis mediating pain desensitization through 5-hydroxytryptamine 3A (5-HT3A) receptor activation in spinal dorsal horn (SDH). Methods A cholestasis model was established by bile duct ligation (BDL) in rats. Pain thresholds of rats were measured after BDL or intrathecally injecting bilirubin in the presence or absence of agonist (mCPBG) and antagonists (ondansetron, bicuculline or CGP55845). Expression of 5-HT3 receptors, and the affinity and binding mode of bilirubin to 5-HT3A receptor were determined. Effects of bilirubin on γ-aminobutyric acid (GABA) pathway and the interactions with 5-HT3A receptor were tested. Results Bilirubin was elevated significantly in both serum and CSF in BDL rats, accompanied with the up-regulation of pain thresholds. Both of 5-HT3A receptor and GABAA receptor antagonists could reverse the increased pain threshold in BDL rats. Further, 5-HT3A and GABAA receptor expressions were increased in BDL rats or intervention with bilirubin. Molecular docking suggested that bilirubin entered the hydrophobic pocket pre-formed in 5-HT3A receptor with potential hydrogen bonding. Bilirubin also increased GABA concentrations in CSF and GABAergic spontaneous inhibitory postsynaptic current in spinal cord, and directly induced inward currents in HEK293 cells which were overexpressed 5-HT3A receptor by lentivirus. Conclusions In conclusion, bilirubin induced pain desensitization in cholestasis by activating 5-HT3A receptor in spinal cord. The activation of 5-HT3A receptor might regulate pain threshold by acting on the GABA pathway.